2014
DOI: 10.1007/82_2014_366
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Science in Understanding Cholera Outbreaks and Evolution of Vibrio cholerae as a Human Pathogen

Abstract: Modern genomic and bioinformatic approaches have been applied to interrogate the V. cholerae genome, the role of genomic elements in cholera disease, and the origin, relatedness, and dissemination of epidemic strains. A universal attribute of choleragenic strains includes a repertoire of pathogenicity islands and virulence genes, namely the CTX–ϕ prophage and Toxin Co-regulated Pilus (TCP) in addition to other virulent genetic elements including those referred to as Seventh Pandemic Islands. During the last de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 107 publications
(128 reference statements)
1
12
0
Order By: Relevance
“…The accessory genome of the analyzed strains essentially constitutes of genomic islands mainly the Vibrio Pathogenicity Islands, toxin co-regulated pilus biosynthesis proteins, the CTX prophage, and resistance genes on the SXT integrative conjugative element (Fig 4). These findings corroborates previous finding [37,39] and confirms that the CTX prophage is not part of the core genome of V . cholerae O1.…”
Section: Resultssupporting
confidence: 93%
“…The accessory genome of the analyzed strains essentially constitutes of genomic islands mainly the Vibrio Pathogenicity Islands, toxin co-regulated pilus biosynthesis proteins, the CTX prophage, and resistance genes on the SXT integrative conjugative element (Fig 4). These findings corroborates previous finding [37,39] and confirms that the CTX prophage is not part of the core genome of V . cholerae O1.…”
Section: Resultssupporting
confidence: 93%
“…Among phenotypic traits distinguishing the 2 biotypes, sensitivity to polymyxin B (50 U) is considered a reliable indicator and stable phenotype for biotyping. Research has shown that the genome of V. cholerae strains is undergoing cryptic changes that influence the strains’ virulence, rapid transmission, and spread ( 4 ). Our previous findings showed El Tor strains with few biotype traits of classical strains ( 5 ).…”
mentioning
confidence: 99%
“…This aligned the cholera outbreak in Nepal and the arrival of Nepalese soldiers in Haiti with the start of the Haitian outbreak (145). WGS provided particularly strong evidence that Nepalese UN peacekeeping troops brought cholera to Haiti (154)(155)(156). The intricacies of this outbreak could not have been solved and the source of the contamination would not have been conclusively identified without the use of a WGS typing approach.…”
Section: Vibrio Choleraementioning
confidence: 93%